What throwing frame configuration should be used to investigate the impact of different impairment types on Paralympic seated throwing? - Tweedy, S. M.; Connick, M. J.; Burkett, B.; Sayers, M.; Meyer, C.; Vanlandewijck, Y. C. (Sports Technology, 2012)
International Paralympic Committee Athletics classification aims to place athletes who throw from a seated position into classes according to how much their neuromusculoskeletal impairments affect that activity, so that impairment severity does not influence competition outcome. Current classification methods are not evidence based and their development requires research in which athletes with varying impairments throw from standardized throwing frame configurations, thereby permitting quantification of impairment impact. Unfortunately athletes throw from highly individualized (not standardized) positions. This study aimed to establish two standardized seating configurations ? one with assistive pole, one without ? which would permit conduct of the required research. Using a custom-built, adjustable throwing frame, 47 non-disabled males self-selected their preferred seated throwing configurations with an assistive pole and without. Seventeen repeated the self-selection process within a week. All then completed three maximal throws from their self-selected configurations. Mean configuration without pole was 34° (seat angle) and 17% sitting height (backrest). Mean configuration with a pole was 32° (seat angle), 15% sitting height (backrest), 75° elbow extension, and 127° pelvic angle (pole position). Results establish the seated throwing configurations preferred by non-disabled people, providing a valid guide for researchers wishing to evaluate the impact of impairment on seated throwing performance.